Hubungan Grading Histopatologi dengan Invasi Limfovaskular Pada Penderita Kanker Payudara di RSUD Al-Ihsan Bandung - Indira Khairana; Yusuf Heriady; Susan Fitriyana (UNISBA Press, 2022)
Abstract. The majority of breast cancer patients come in an advanced stage which can give a poor prognosis to the patient. The purpose of this study was to determine the relationship between histopathological grading with lymphovascular invasion in breast cancer patients at Al-Ihsan Hospital Bandung which was indicated as a prognostic factor for breast cancer. This study uses an observational analytical method with cross-sectional approach. The data was taken via medical records and histopathology lab results from January 2020 - December 2020. The sample selection method used a total sampling of 76 records that met the inclusion and exclusion criteria. The results showed that the majority of breast cancer patients at Al-Ihsan Hospital Bandung were histopathological grade 3 (71.1%) and positive lymphovascular invasion (82.9%). Statistical tests were carried out using fisher’s exact test. The results showed that there was a significant relationship between histopathological grading (p=0,039) with lymphovascular invasion in breast cancer patients at Al-Ihsan Hospital Bandung. The conclusion in this study is that there is a relationship between histopathological grading with lymphovascular invasion. Abstrak. Pasien kanker payudara mayoritas datang dalam keadaan stadium lanjut sehingga dapat memberikan prognosis buruk kepada penderita. Tujuan dari penelitian ini untuk mengetahui hubungan grading histopatologi dengan invasi limfovaskular pada penderita kanker payudara di RSUD Al-Ihsan Bandung yang diindikasikan sebagai faktor prognostik kanker payudara. Penelitian ini menggunakan metode observasional analitik dengan rancangan cross-sectional. Data berupa rekam medik dan hasil lab histopatologi yang diambil dari Januari 2020 – Desember 2020. Total sampel penelitian berjumlah 76 pasien yang diambil melalui total sampling dan telah memenuhi kriteria inklusi maupun eksklusi. Hasil penelitian menunjukkan mayoritas penderita kanker payudara di RSUD Al-Ihsan Bandung memiliki derajat histopatologi 3 (71,1%) dan invasi limfovaskular positif (82,9%). Uji statistik dilakukan dengan menggunakan uji fisher’s exact test. Hasilnya menunjukkan terdapat hubungan yang bermakna grading histopatologi (p=0,039) dengan invasi limfovaskular pada penderita kanker payudara di RSUD Al-Ihsan Bandung. Kesimpulan pada penelitian terdapat hubungan grading histopatologi dengan invasi limfovaskular.